An improved sealed quartz‐tube method for the determination of hydrogen isotopes in water. (14th August 2020) - Li, Hongwei; Feng, Lianjun
Abstract: Hydrogen stable isotope analysis has been a valuable tool in the fields of geochemistry and ecological research as well as many other research fields. The methods are mainly divided into the dual‐inlet method (off‐line method) and continuous flow method. The dual‐inlet method is complicated and inefficient, but it is still important because of its high precision and wide application range. Although the continuous flow method improves the experimental efficiency, the memory effect is noticeable and the accuracy is reduced. An improved sealed quartz‐tube method is proposed in this paper. The sample is sealed in a capillary tube and placed in a quartz tube containing chromium powder. It is then packaged, evacuated, reacted at a high temperature, and analyzed for hydrogen isotope ratio. Excellent data accuracy, good reproducibility (<1‰), and no memory effect occurred in the method. The process is relatively simple, and the experimental efficiency is greatly improved, which provides an effective method for the analysis of hydrogen isotopes in complex liquid samples.